Divergences between official sources in the number of physicians and medical density in the municipalities of Rondônia at the end of 2020 (Research, Society and Development, 2022)
Objective: Calculate and compare the density of physicians/thousand inhabitants in the municipalities of Rondônia in 2020 and verify the divergences between the official data sources from 2010 to 2020. Methods: Ecological study in the municipalities of Rondôniausing the databases of DATASUS, of Federal Council of Medicine (CFM), and IBGE; the Excel spreadsheet was used for tabulation and statistical calculations; the geoprocessing tool QGIS was used to interpolate the geographic data with the Inverse Distance Weighting method. Results: In Rondônia, there is a divergence of 500 physicians between the CFM and TABNET bases and the municipality of Cacoal, in the countryside, has the highest density in the state with 4.13 physicians/thousand inhabitants. The interpolation shows greater medical density along the margins of the main highway that provides access to the state - the BR-364. Conclusion: It is not the capital, Porto Velho, which has the highest density of physicians/thousand inhabitants. CFM always has a greater number of physicians than TABNET.